Views of Clergy And Medical School Claims In Bandung Regency on Ruqyah Therapy as a Means of Treating People With Mental Disorders - Andriyani, Fitriah; Ashari, Oky; Audyta, Rindi; Nuryani, Tiya; Octaviani, Tiara; Alawiyah, Tuti; Nurul, Yasinta; Wahyuni, Zahra; Supriyadi, Tedi (Program Pascasarjana UIN Sumatera Utara, 2024)
The aim of this research is to find out the perspectives of ulama and medical personnel regarding the treatment of people with mental disorders (ODGJ) through ruqyah therapy. This research method uses a qualitative research design by gathering information from sources using direct interviews. The participants who took part in this research included 3 ulama, 1 ruqyah practitioner, and 1 medical staff. This research was conducted at the Manarul Huda Islamic Boarding School, the Addzimat Da'I Indonesia Islamic Boarding School, the AR-Rohmat Islamic Boarding School, the Ruqyah Practitioner's House and at the zoom meeting media. The Rugyah method is used as a medium for healing mental disorders. Ruqyah itself is one that uses verses from the Al-Qu'an and prayers taught by the Prophet Muhammad. Ruqyah therapy is recommended by ulama because it has a positive impact, but it also needs to be integrated with conventional medical treatment. Further observation and research is needed in the application of ruqyah therapy to treat mental disorders.